OC-039 Altered gene expression levels of MAD2, BUB1, aurora kinase A and B in early gastric cancers. (23rd September 2015) - Somasekar, A; Chatterjee, A; Williams, L; Griffiths, P; Williams, J; Jenkins, G
Abstract : Introduction: Losses and/or gains of whole chromosomes (aneuploidy) are extremely common in most cancers. Indeed aneuploidy is thought to occur early in carcinogenesis and the genetic instability induced is thought to provide a pool of selectable clones for tumour evolution. We have been interested in aneuploidy as a biomarker for GI tract cancer for some time. It is believed that alterations in the expression of key components of the mitotic checkpoint drive aneuploidy, by impairing the ability of this checkpoint to prevent chromosome mis-segregation. Here we aimed to correlate gene expression levels of the mitotic checkpoints MAD2, Bub1, aurora kinase A and B with aneuploidy levels and histology in premalignant gastric tissues. Methods: We collected over 50 cytology brush samples of gastric mucosa during routine endoscopic examination. We examined aneuploidy levels in these exfoliated cells using fluorescent in situ hybridisation, specifically looking at copy numbers of chromosome 1. Concurrently, during endoscopy, biopsy samples were obtained from the same gastric epithelium for histological assessment and for CLO testing and further biopsies were obtained and used to extract RNA to determine mitotic checkpoint gene expression levels using the real-time PCR. Specifically the expression levels Mad2, Bub1, aurora kinase A and B were assessed. Results: Aneuploidy levels mirrored histological progression in the stomach as previously described (from an average of 2.6% in normal gastric epithelium to over 6% in intestinal metaplasia/atrophic gastritis). RNA was extracted from 46 samples for mitotic checkpoint gene expression analysis. Mad2 and Bub1 expression levels were found to be decreased significantly in the small number of samples with intestinal metaplasia. We also demonstrated that the levels of Mad2 and Bub1 were also diminished in the 28 patients with gastritis. Conversely, Aurora kinase A and B were upregulated in the H pylori infected tissues in particular, compared to histologically normal tissue. Comprehensive data analysis is now underway comparing mitotic checkpoint expression to histology, aneuploidy level and to key clinical parameters. Conclusion: Mitotic checkpoint dysregulation occurs in pre-malignant gastric tissue concurrently with rising levels of aneuploidy. These mitotic checkpoint abnormalities may underlie the induction of aneuploidy and may represent the mechanism by which chromosomal instability is induced in early neoplasia.